Emergencies in otorhinolaryngology - Sahoo, G. C. (Jaypee Brothers Medical Publishers (P) Ltd, 2014)
Comprehensive guide to emergencies in otorhinolaryngology for practising ENT specialists. Twelve chapters cover key aspects in the diagnosis and management of common ear, nose and throat emergencies